Pengaruh Matos terhadap Peningkatan CBR (California Bearing Ratio)dan Sifat Kedap Airpada Tanah Sekitar Rawa Pening - Erwin Harris Saputra; Lie Sanders Deckcrealy; Djoko Suwarno; Budi Setiyadi (Universitas Katolik Soegijapranata Semarang, 2018)
Rawa Pening soil contains peat has low level of California Bearing Ratio (CBR) and high permeability so it is less suitable for embankment. Above the embankment functioned as a road body. This study adds cement and matos (normal) to increase soil bearing capacity. (50%), 50% G 50% Cement (C) 8%, TSRP 50% + G 50% + C 8% + Matos (M) 2%, 4% and 6%. CBR soaked, normal results obtained CBR 2.99% while the CBR requirement of 5.44%. Addition of C 8% adds CBR value to 9,25%, while addition of M 2% increase CBR value equal to 8,9%, M 4% yield CBR become 16% and M 6% get CBR equal to 16%. Low compaction, normal soil undergoes seepage after a day, compaction is undergone seepage after 3 days and standard compaction does not undergo seepage for 7 days. The most optimal result, with stabilization of C 8% and M 4%. Addition of M 2% is not effective or equal to 8% cement. The addition of M 6% equals M 4%.